Introduction to the explicit finite element method for nonlinear transient dynamics - Wu, Shen R; Gu, Lei (WILEY, 2012)
This text specifically addresses the explicit finite element method for nonlinear transient dynamics. The book aids readers in mastering the explicit finite element method as well as programing a code without extensively reading the more general finite element books.